Comments on Contemporary Political Theology - AN, Ximeng (Journal of Research for Christianity in China (JRCC), 2025)
The article belongs to a fragment of the development history of Christian theology. Political theology can be traced back to the Stoics.In the twentieth century Schmidt restored political theology.Political theology is still the European trend of thought.European society was reformed through various waves of criticism.Themes of political theology gained renewed attention in the 1960s.The emphasis on politics is once again having an impact.Modern political theology puts forward a new view on the relationship between theology and politics.Political theology is different from forcing theologians and pastors to "talk politics".Modern political theology pays more attention to this side than to the imagination of the other side.More concrete than abstract.Public more than private.Practice is more than speculation.History is more concrete than metaphysical.The contemplation of suffering is greater than the contemplation of heaven.The former political theology identifies with the present situation, while the new political theology is critical, practical, revolutionary, rebellious, liberating, radical and public theology.Political theology has accepted the critical, revolutionary, practical and public nature of Marxism.They take Marx’s religious criticism seriously.It was also critical of church institutions and theological traditions."Deprivatization" is also the creed of all political theologians.Moltmann stresses the distinction between old and new political theology.The old, outdated political theology is called political religion.The "submission" of religion to the secular society is the political religion that takes religion as its handmaid.On the other hand, European political theology lacks the practical social consequences of the gun-toting priests of liberation theology.